2005
DOI: 10.1111/j.1600-0897.2005.00260.x
|View full text |Cite
|
Sign up to set email alerts
|

Embryo Aneuploidy Screening for Unexplained Recurrent Miscarriage: A Minireview

Abstract: Recurrent miscarriage is associated with a higher incidence of chromosomally abnormal embryos. In vitro fertilization (IVF) plus PGD is an important step in the management of these couples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(46 citation statements)
references
References 44 publications
(61 reference statements)
1
41
0
4
Order By: Relevance
“…Especially this is due to the fact that carriers of BRT have a risk of partial trisomy or partial monosomy for chromosomal regions involved in the translocation due to meiotic segregation. Most of the spontaneous miscarriages are caused due to chromosomal abnormalities in the embryo or foetus [8]. The genetic etiology for multiple spontaneous miscarriages includes an unbalanced chromosomal rearrangement which may be the result of one parent being carrier for BRT [9].…”
Section: Discussionmentioning
confidence: 99%
“…Especially this is due to the fact that carriers of BRT have a risk of partial trisomy or partial monosomy for chromosomal regions involved in the translocation due to meiotic segregation. Most of the spontaneous miscarriages are caused due to chromosomal abnormalities in the embryo or foetus [8]. The genetic etiology for multiple spontaneous miscarriages includes an unbalanced chromosomal rearrangement which may be the result of one parent being carrier for BRT [9].…”
Section: Discussionmentioning
confidence: 99%
“…Accurate chromosome segregation is the crux of mitosis -failure causes genetic disorders, spontaneous abortions and cancer (Kops et al, 2005;Rubio et al, 2005;Shah et al, 2003;Weaver and Cleveland, 2006;Weaver et al, 2007). To allow accurate segregation, sister chromatids must remain cohered from their inception, which occurs in S-phase, until anaphase ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Gianaroli et al (2005) obtained ~30% pregnancy rate with a high percentage (66%) of chromosomally abnormal embryos. Rubio et al (2005) also observed a higher percentage of abnormal embryos and lower pregnancy and implantation rates in the RSA group, when compared to patients with sex-linked diseases as controls. A prospective cohort study implied that there is no direct impact of PGD-AS on RSA patients irrespective of the maternal age (Platteau et al, 2005).…”
Section: Discussionmentioning
confidence: 91%